PERBANDINGAN EFEKTIVITAS PEMBERIAN REBUSAN JAHE MERAH DAN DAUN MINT DENGAN JERUK NIPIS DAN MADU TERHADAP MUAL MUNTAH PADA IBU HAMIL TRIMESTER I DI PUSKESMAS WAEPANA, NGADA, NTT - Ursula Orcena Mau Soa; Rizky Amelia; Dhita Aulia Octaviani (JURNAL KEBIDANAN, 2018)
Nausea and vomiting is a normal experienced by 50-80% of first trimester pregnant women. Pregnant women condition is very vulnerable on drugs, so the pregnant women should usecomplementary therapies to reduce nausea and vomiting. Red ginger and mint leaves with lime and honey is herbal medicine can be used by first trimester pregnant women to reduce nausea and vomiting. This research intended to determine the effectiveness comparison of red ginger decoction and mint leaves with lime and honey to nausea and vomiting on first trimester pregnant women.Quasi-Experiment method was used, two groups of pre-test and post-test design for this research. The sample in this research wasto 22 respondence of women at the first trimester pregnancy. Purposive Sampling was used for sampling. The data analysis used Mann-Whitney and Wilcoxon test. Based on the research result, the mean value on red ginger and mint before and after was 3.55 and  3.09, and the mean value of lime and honey before and after  was 3.35 and 2.09, with p-value of (0.004) α (0.05) and Z count value: -3.014. It means that there was difference between red ginger and mint leaves with lime and honey in reducing nausea and vomiting on first trimester pregnant women at Waepana Community Health Center, Ngada Regency, East Nusa Tenggara. With giving boiled ginger and mint more effective.From the research results, it was expected that health workers need to provide health education to pregnant women about non-pharmacological methods to overcome nausea and vomiting which is by providing red ginger decoction and mint leaves with lime and honey at home.